Perforated Meckel's Diverticulum Lithiasis: An Unusual Cause of Peritonitis. (29th May 2013) - Mathuram Thiyagarajan, Umasankar; Ponnuswamy, Amirthavarshini; Bagul, Atul; Ponnuswamy, Prabakar
Abstract : Meckel's diverticulum is the commonest congenital malformation of gastrointestinal tract and represents a persistent remnant of the omphalomesenteric duct. Although it mostly remains silent, it can present as bleeding, perforation, intestinal obstruction, intussusception, and tumours. These complications, especially bleeding, tend to be more common in the paediatric group and intestinal obstruction in adults. Stone formation (lithiasis) in Meckel's diverticulum is rare. We report a case of Meckel's diverticulum lithiasis which presented as an acute abdomen in an otherwise healthy individual. The patient underwent an exploratory laparotomy which revealed a perforated Meckel's diverticulum with lithiasis; a segmental resection with end-to-end anastomosis of small bowel was performed. Patient recovery was delayed due to pneumonia, discharged on day 20 with no further complications at 6 months following surgery.